Influence of a probiotic/trace mineral mixture on growth performance and Salmonella choleraesuis shedding in nursery pigs - Robert D Goodband; Jim L Nelssen; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
We tested a probiotic/trace mineral mixture using a bacterial challenge model in high-health status pigs. We examined the influence of the mixture on growth performance, hematologic parameters, haptoglobin concentration, and Salmonella choleraesuis shedding in nursery pigs. A successful model of S. cholereasuis challenge was established. However, the probiotic/trace mineral mixture did not influence growth performance, bacterial shedding, or other parameters examined in this experiment.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Salmonella choleraesuis; Probiotics; Trace minerals